From Product Description to Conversational Tone: Exploring The Register Language Of Indonesian Skincare Seller - Maghfiroh, Annisatul (Language Horizon: Journal of Language Studies, 2022)
This research aimed to investigate the linguistics form, meaning, and motive used by Indonesian skincare sellers on TikTok shops. The researchers employed qualitative research design with the object was product description and video ads by skincare brand. The researcher collected the data through documentation. The researchers analyzed the data by identified the linguistic forms by classifying the data and determining which ones belonged to register words and phrases. Second, analyzed the meaning of the registers by considering the context of the data. Third, applied Chen’s (2020) motivation model theory to explore the underlying motives behind the use of these registers Therefore, the researchers revealed the high frequency of linguistics forms of the register was in adjective. The researchers found one noun, four adjectives, one compound, two abbreviation, and two noun phrases. Furthermore, the reason behind the way sellers use language is to give clear and reliable details about their skincare products, which is called transactional motivation. Additionally, sellers also have another motive called interactional motivation. They strive to establish, uphold, and enhance the public perception of their brand and products.